2018
DOI: 10.1177/1362168818802469
|View full text |Cite
|
Sign up to set email alerts
|

The revision and transfer effects of direct and indirect comprehensive corrective feedback on ESL students’ writing

Abstract: This study investigated the short-term and delayed effects of comprehensive written corrective feedback (WCF) on L2 learners’ revision accuracy and new pieces of writing (i.e., the transfer effect of feedback). Three types of feedback were compared: direct feedback and two types of indirect feedback that differed in their degree of explicitness (i.e., underlining only and underlining+metalinguistic cues). Fifty-three intermediate level learners of English as a second language (ESL) were divided randomly into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
134
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 56 publications
12
134
1
Order By: Relevance
“…The findings of this study are in line with those of several previous studies (e.g., Bitchener, 2008;Bitchener & Knoch, 2008, 2009Ellis et al, 2008;Karim & Nassaji, 2018;Sheen, 2007Sheen, , 2010 which confirmed the effects of WCF and its types (direct and indirect) on different language learning aspects, such as grammatical structures, language production, writing skills and accuracy in revising. These studies collectively provide further counter-evidence to what Truscott (1996Truscott ( , 2001Truscott ( , 2007 noted with regard to the inefficacy of written CF.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study are in line with those of several previous studies (e.g., Bitchener, 2008;Bitchener & Knoch, 2008, 2009Ellis et al, 2008;Karim & Nassaji, 2018;Sheen, 2007Sheen, , 2010 which confirmed the effects of WCF and its types (direct and indirect) on different language learning aspects, such as grammatical structures, language production, writing skills and accuracy in revising. These studies collectively provide further counter-evidence to what Truscott (1996Truscott ( , 2001Truscott ( , 2007 noted with regard to the inefficacy of written CF.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, more studies have been performed to investigate the effectiveness of WCF in developing learners' accuracy in L2 development that followed research designs like the ones used in investigating various forms of oral corrective feedback (CF). A consistent evidence provided by these recent studies (Sheen, 2007(Sheen, , 2010Bitchener, 2008;Ellis et al, 2008;Sheen, Wright, & Moldawa, 2009;Bitchener & Knoch, 2009a, 2009bVan Beuningen, de Jong, & Kuiken, 2012;Shintani, Ellis, & Suzuki, 2014;Stefanou & Revesz, 2015;Karim & Nassaji 2018 ;Westmacott, 2017;Banaruee, Khatin-Zadeh, Ruegg, 2018) revealed that CF has performed a significant role in assisting learners to acquire grammatical features thus improving their linguistic proficiency in the target structure of the language.…”
Section: Introductionsupporting
confidence: 69%
“…Non-grammatical structures of the language have also gained the attention of SLA scholars. Several studies were conducted to investigate the effect of direct and indirect WCF on non-grammatical structures such as vocabulary (Ghandi & Maghsoudi, 2014;Septiana, Sulistyo & Kadarisman, 2016;Banaruee et al, 2018;Cerezo et al, 2019), punctuation (Karim & Nassiji, 2018), sentence structures (Cerezo et al, 2019), spelling errors (Karim & Nassaji, 2018;Ghandi & Maghsoudi, 2014), and word choice (Ruegg, 2015;Karim & Nassaji, 2018;Van Beuningen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Vinagre and Munoz (2011), Eslami (2014), Jamalinesari, et.al (2015) and Tan and Manochphinyo, (2017) alleged that indirect corrective feedback is more effective than direct corrective feedback. Nevertheless, Karim, andNassaji, (2018), Van Beuningen, et al (2012) and Vyatkina (2010) assumed that both direct and indirect corrective feedback are similar in their effectiveness in developing grammatical accuracy in writing. Such perplexing results sustained the need for new studies comparing the effectiveness of direct and indirect corrective feedback in reducing learners' grammatical errors in writing.…”
Section: Introductionmentioning
confidence: 99%